Compensation : theory, evidence, and strategic implications - Gerhart, Barry A.; Rynes, S. (Sara) (Foundations for organizational science., 2003)
'Compensation' provides a comprehensive, research-based review of both the determinants and effects of compensation. Combining theory and research from a variety of disciplines, the text examines the three major compensation decisions - pay level, pay structure and pay delivery systems.